2019
DOI: 10.1155/2019/6857417
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobinopathies in the North of Morocco: Consanguinity Pilot Study

Abstract: Consanguinity is a social behavior characterized by the arrangement of marriages between relatives. It coincides generally with the geographic distribution of recessive genetic diseases as it increases the likelihood of homozygosis and, consequently, the incidence of their pathologies in the population. In this pilot study, we assess the effect of inbreeding on the burden of hemoglobinopathies in Northern Morocco. From January 2016 to December 2018, 197 children born in the studied region to three ancestral ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In a study conducted in Morocco recruiting the parents of 197 children diagnosed with hemoglobinopathies, it was reported that 50.25% of the sample of parents were related to their partners. 16 This finding is similar to our findings, illustrating the important cultural influence in supporting consanguineous marriages.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted in Morocco recruiting the parents of 197 children diagnosed with hemoglobinopathies, it was reported that 50.25% of the sample of parents were related to their partners. 16 This finding is similar to our findings, illustrating the important cultural influence in supporting consanguineous marriages.…”
Section: Discussionsupporting
confidence: 92%
“…A 2016-2018 study of consanguinity in the hemoglobinopathy population found, however, that consanguinity in the parents of hemoglobinopathy patients was much higher (50.25%) than in the normal population. This study also documented that, while high, this is a 14.22% decrease from the previous generation, presumably due to improving genetic information and education (Laghmich et al 2019b).…”
Section: Morocco (Kingdom Of Morocco)supporting
confidence: 61%
“…This finding is consistent with the previous study which showed that the consanguinity rate in Eastern Morocco region is higher than the national average (29.58% vs. 22.79%) (Mohammed et al, 2019 ; Talbi et al, 2007 ). Thereby, it is not surprising to see a strong occurrence of autosomal recessive diseases such as thalassemia in our population (Habibeddine et al, 2018 ; Jaouad et al, 2009 ; Laghmich et al, 2019 ).…”
Section: Discussionmentioning
confidence: 63%